Paradigma Pendidikan Era Learning Society 5.0: Model STEAM sebagai Internasional Best Practice dalam Smart Education - Ghasa Faraasyatul ‘Alam; Ali Imron; Achmad Supriyanto; Mustiningsih Mustiningsih (Universitas Negeri Malang, 2023)
Abstract: The era of the industrial revolution which has now reached 5.0 demands changes in all aspects marked by the use of digital technology. This research aims to prepare education for the era of learning society 5.0 in the challenges of new paradigms in the context of the 21st century skill picture which can later be of long-term benefit to be able to improve the quality of education and unite international level education and the application of modern technology as a whole at various levels of education that have also implemented best practices for learning models in a related educational institution. Researchers use a type of literature study approach by applying the literature review method to be able to get the latest information and quality data with the most accurate and reliable sources. Data that has been collected and neatly arranged will soon be analyzed using systematic steps, including identifying research topics, determining the focus of literature, searching for research supporting sources, assessing the quality of sources, presenting research results, and drawing conclusions. There are four research results of the educational paradigm of the learning society 5.0 era, including: (a) International best practices in education; (b) Changes in the role of educators; (c) Optimization of smart education; and (d) Implementation of the STEAM model.Keywords: educational paradigm, learning society 5.0, STEAM model, international best practice, smart educationAbstrak: Era revolusi industri yang kini sudah mencapai 5.0 menuntut adanya perubahan dalam segala aspek ditandai dengan adanya pemanfaatan teknologi digital. Penelitian ini bertujuan untuk mempersiapkan pendidikan era learning society 5.0 dalam tantangan-tantangan paradigma baru pada konteks gambaran keterampilan abad ke-21 yang nantinya dapat bermanfaat jangka panjang untuk dapat meningkatkan mutu pendidikan serta menyatukan pendidikan tingkat internasional dan penerapan teknologi modern secara menyeluruh diberbagai jenjang pendidikan yang juga sudah mengimplementasikan best practice untuk model-model pembelajaran di suatu lembaga pendidikan terkait. Peneliti menggunakan jenis pendekatan studi pustaka dengan menerapkan metode literature review untuk bisa mendapatkan informasi terbaru serta data yang berkualitas dengan sumbersumber terakurat dan terpercaya. Data yang sudah terkumpul dan tertata rapi akan segera dilakukan analisis dengan menggunakan langkah-langkah sistematis antara lain adalah melakukan identifikasi topik penelitian, menentukan fokus dari literatur, pencarian sumber-sumber penunjang penelitian, penilaian kualitas sumber, penyajian hasil penelitian, dan penarikan kesimpulan. Terdapat empat hasil penelitian paradigma pendidikan era learning society 5.0 antara lain: (a) Internasional best practice dalam pendidikan; (b) Perubahan peran pendidik; (c) Optimalisasi smart education; dan (d) Implementasi model STEAM.Kata kunci: paradigma pendidikan, learning society 5.0, model STEAM, internasional best practice, smart education